Signalling Moderation: UK Trade Unions, 'New Labour' and the Single Currency - Steve Coulter (London School of Economics and Political Science (LSE), European Institute, 2016)
The paper examines why, and under what conditions, certain interest groups adopt positive positions on international economic issues. It provides a case study of how UK trade unions formed their preferences on membership of the EMU. Previous explanations of this have tended to emphasise the international dimension – either the material benefits on offer or whether or not they became 'Europeanised'. A few authors are now exploring domestic political explanations instead. The paper builds on this growing literature to argue that the TUC, the peak association of organised labour in the UK, became extremely pro-EMU as part of a strategy to demonstrate its moderation to Tony Blair's centrist 'New' Labour party, which was distancing itself from unions to court business.
Keywords: 330; New Labour; trade unions; interest group politics; EMU; Europeanisation